Thermal conductivity modeling of hybrid organic-inorganic crystals and superlattices. (November 2017) - Qian, Xin; Gu, Xiaokun; Yang, Ronggui
Abstract: Hybrid organic-inorganic materials have attracted intensive research interests due to the superb physical properties that take advantage of both organic and inorganic components and their promising applications in functional devices such as light emitting diodes, solar cells, and flexible thermoelectrics. Understanding thermal transport in hybrid materials is of importance for both the reliability and the performance of the hybrid material-based systems. The organic-inorganic hybrid materials can be classified as nanocomposites, superlattices and crystals depending on the strength of organic-inorganic bonding and the feature size of organic and inorganic components. Previous research on thermal transport mainly focus on hybrid nanocomposites where phonon-interface scattering dominates the thermal transport process. However, in hybrid superlattices and crystals, organic and inorganic components are blended at the atomic scale by chemical bonds without a clear interface, and the phonon transport physics is not well understood. This article reviews the recent progress in ab-initio modeling on phonon transport in hybrid crystals and superlattices. The predicted thermal conductivity of II–VI based organic-inorganic semiconductors, organometal perovskites and organic-intercalated TiS2 superlattices are reviewed and compared with experimental data when available. This review provides guidance for modeling thermal conductivity of materials with complex atomic structures from the first principles, which could be a good tutorial for both graduate students and experienced researchers who are interested in thermal energy transport in emerging hybrid materials. Graphical abstract: Highlights: First review on modeling thermal transport in hybrid crystals and superlattices. Integrated DFT-MD method is developed to handle structural complexity. Organic/inorganic components meditate thermal transport in hybrid materials.